Effect of Carbon Nanotube Dispersions to the Palm Oil Diesel-Biodiesel Blend Properties - Ahmad Basirul Subha, Alias; Thegaraju, D.; Sharma, K. V. (2013)

(untitled)
This paper reports on the use of Carbon Nanotubes (CNT) as an additive to the palm oil dieselâbiodiesel fuel blends and its effects to the fuel properties. The tested biodiesel fuels were prepared by dispersing CNT into the diesel-biodiesel fuel blends at five different concentrations of 0.005% vol, 0.010% vol, 0.015% vol, 0.020% vol, 0.025% vol respectively and have their properties tested and compared against the standard baseline pure palm oil biodiesel and diesel fuel. Three blending proportions of B100 (100% palm oil biodiesel by volume percentage), B20, and B10 were used for experimentations. Results shown that the thermal conductivity and flash point of the fuels dispersed with CNT have increased with higher dispersion concentration of CNT. The pour point data however, shown a decrement trend when dispersed with CNT at higher concentrations and suspension of CNT in blends has also increased the fuelâs cetane number as well as fuelâs Heating Value (HV). Dispersion of CNT as additive has improved the fuel properties and operational characteristics of palm oil biodiesel fuel and its blends